Regional monitoring results of population exposure doses from ionizing radiation sources - J. I. Stepkin; V. K. Kuzmichev; O. V. Klepikov (Радиационная гигиена)
The study was aimed at personnel and population exposure dose assessment from all main activities and radiation sources in Voronezh region. Assessment of Voronezh Region’s population exposure doses from ionizing radiation sources was conducted using the data of the Federal healthcare institution “Voronezh Region’s Hygiene and Epidemiology Center” on the basis of information derived from forms of Federal state statistical observation over 2010- 2014: No.1-DOZ “Information on personnel exposure doses under normal operation of technogenic ionizing radiation sources” No.3- DOZ ‘Information on patients’ exposure doses during X-ray – radiological tests”, No.4- DOZ “Information on population exposure doses from natural and technogenically impacted background” and the data from Voronezh Region’s radiation-hygienic passport over 2010–2014. It was established that the situation related to Voronezh Region’s ionizing sources impact remains stable over the recent 5 years. Dose interval distribution of groups A and B personnel headcount demonstrated that 58.2% of persons are exposed to doses in the range between 1 and 2 mSv/year and 3.6% to 2-5 mSv/year, respectively. The median yearly effective doses of natural human radiation exposure are in the intervals between 2.350 and 4.480 mSv per year which is typical for this territory. The median effective dose from medical tests per one treatment in different years is between 0.30 and 0.41 mSv. X-ray and computer tomography make the largest contribution into collective population medical radiation dose- 35.6% and 27.8% respectively. On the whole population’s major dose contributors are natural ones. Natural factors’ annual contribution into annual effective dose is between 74.96 and 79.68 %.